The conflictual triangular relationship between the United Nations Security Council, the International Criminal Court and the African Union through the lens of cooperation : the implications for international criminal justice - Tladi, Dire (University of Pretoria, 2024)
Thesis (PhD (International Law))--University of Pretoria, 2024.